Fear of Negative Evaluation and Social Anxiety in the Context of the Revised Reinforcement Sensitivity Theory - Ranđelović, Kristina M.; Želeskov Đorić, Jelena D. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The main goal of this research paper is to examine the predictive power of personality traits in relation to fear of negative evaluation and social anxiety. The revised Reinforcement Sensitivity Theory (rRST) postulates the existence of three major personality systems - Behavioural Inhibition System (BIS), Behavioural Activation System (BAS), and Fight-Flight-Freeze System (FFFS). In order to assess the personality traits, the Reinforcement Sensitivity Questionnaire was used (RSQ). Fear of negative evaluation was assessed using the Fear of Negative Evaluation Scale – Brief form (FNE-B), while social anxiety evaluation was obtained by Social Anxiety Scale (SA2). The sample consisted of 222 psychology students engaged in 1st and 2nd year of studies at the University of Niš and the University of Novi Sad. In order to respond to the research questions, two separate multiple regression analyses were performed. In both analyses, personality traits were the predictors, while the differences were linked to the criteria variables – Model1 – fear of negative evaluation, and Model2 – social anxiety. Both models were statistically significant. According to the results, Fear of negative evaluation model explains a total of 41% of the criteria variance, while Social anxiety model explains 46% of the criteria variance. In both models, BIS stands out as the statistically significant and the best predictor. When comparing the results of both models, the differences relate to the second significant predictor. Namely, Fight response stands out in the first model, while Freeze response stands out in the second one. The obtained findings are discussed and interpreted in the context of rRST.